2022
DOI: 10.1111/bjh.18526
|View full text |Cite
|
Sign up to set email alerts
|

Trend of circulating CD34+ cells in patients with myelofibrosis: Association with spleen response during ruxolitinib treatment

Abstract: ABL1-negative myeloproliferative neoplasms (MPNs) are already known to be variably characterised by an increase in peripheral blood (PB) and bone marrow (BM) progenitor cells. More specifically, in patients with myelofibrosis (MF) it has already been reported that the number of circulating haematopoietic precursors is consistently high, with a relative circulating CD34 + cells count of 0.015 × 10 9 /L as the most frequently used criterion to discriminate between MF and other MPNs. 1 According to the 2016 World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(84 reference statements)
0
3
0
Order By: Relevance
“… 35 Ethical concerns discourage aggressive procedures to obtain HSCs from bone marrow from these patients, but some HSCs are present and could be isolated from non-mobilized peripheral blood. 64 , 65 , 66 Purified HSCs were exposed to R-GPIX to track lentiviral transduction. Despite the reduced number of starting HSCs, we could recover CD41-GPIX expression in EGFP + MKs and platelets.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Ethical concerns discourage aggressive procedures to obtain HSCs from bone marrow from these patients, but some HSCs are present and could be isolated from non-mobilized peripheral blood. 64 , 65 , 66 Purified HSCs were exposed to R-GPIX to track lentiviral transduction. Despite the reduced number of starting HSCs, we could recover CD41-GPIX expression in EGFP + MKs and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent retrospective study, a positive correlation has been found between peripheral blood CD34 cells and spleen length in both PMF and SMF, thus identifying a possible tool facilitating the assessment of spleen response more objectively than deep palpation of the abdomen ( 41 ).…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…
We read with great interest the findings of the Iurlo et al 1 prospective cohort study, where the number of circulating CD34 + cells increased briefly and then returned to the pretreatment level during ruxolitinib treatment. Furthermore, the authors found a positive correlation between the change in the number of circulating CD34 + cells and the degree of splenomegaly during the first 6 months of treatment.A relative circulating CD34 + cell count of 0.015 × 10 9 /L is the most frequently used criterion to discriminate between myelofibrosis (MF) and other myeloproliferative neoplasms.
…”
mentioning
confidence: 99%